2015
DOI: 10.1007/s10620-015-3755-0
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility of Performing Colorectal Endoscopic Submucosal Dissection Without Previous Experience in Performing Gastric Endoscopic Submucosal Dissection

Abstract: Colorectal ESD can be safely and effectively performed by an endoscopist having extensive experience in colonoscopy-related procedures even without previous experience of gastric ESD. Meticulous case selection for ESD novice and active supervision by expert endoscopists during the initial learning period may minimize the risk of perforation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 44 publications
1
26
2
2
Order By: Relevance
“…Yang et al . also reported the feasibility of colorectal ESD carried out by an endoscopist without experience in gastric ESD . However, different from our study, more than 100 colorectal ESD were needed to become proficient.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Yang et al . also reported the feasibility of colorectal ESD carried out by an endoscopist without experience in gastric ESD . However, different from our study, more than 100 colorectal ESD were needed to become proficient.…”
Section: Discussioncontrasting
confidence: 65%
“…Yang et al also reported the feasibility of colorectal ESD carried out by an endoscopist without experience in gastric ESD. 20 However, different from our study, more than 100 colorectal ESD were needed to become proficient. As Ohata et al have emphasized, 21 supervision by experts might contribute to the present better results.…”
Section: E Ndoscopic Mucosal Resection Is the Standard Endoscopic Trecontrasting
confidence: 74%
“…B. wurden in einer Arbeit zur EMR freie Perforationen von 0,3 % und noch gedeckte tiefe murale Läsionen (Target-sign, erhaltene Serosalamelle) von insgesamt 3 % beschrieben [38]. Mit zunehmender Invasivität steigt das Risiko weiter an und erreicht bei einer kolorektalen ESD eine Inzidenz von 5 % bis zu 16 % [42][43][44]. Auch bei der ERCP besteht ein relativ hohes Perforationsrisiko in der Größenordnung von etwa 1 %, vor allem bei Ausführung einer Papillotomie [21,22,45].…”
Section: Introductionunclassified
“…It is difficult to determine the exact learning curve for colorectal ESD as most studies involve endoscopists already experienced in upper gastrointestinal ESD. However, training in ESD is feasible without significant prior experience of upper gastrointestinal ESD 119,120…”
Section: Introductionmentioning
confidence: 99%